DR.JEKYLL’S INDIVIDUALISM AND ITS BAD IMPACTS ON SELF AND OTHERS IN ROBERT LOUIS STEVENSON’S "STRANGE CASE OF DR.JEKYLL AND MR.HYDE" - IVANA SURYALARAS WIDYASTUTI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2018)
Abstract Individualism has been understanding and has been already applied by people in particular countries their habit and personality. Individualism centers on “self-concept” to persist on life. This study aims to represent Dr.Jekyll’s individualistic personality and bad impacts on self and others because of his personality. This study adapts individualism approaches by Thomas Hobbes “Leviatan” and John Stuart Mill “On Liberty” and others thinkers to support the study. This study will analyze on how individualism is represented through Dr.Jekyll and how the bad impacts on himself and others because of his individualist personality. The writer uses three components for defining individualism in Dr.Jekyll, which are independent, loner, and uniqueness. Then the bad impact is alienated into two parts (Self and other) in order to clarify how individualism brings bad situation for the characters. The result performs that Dr.Jekyll is truly acknowledged as individualist through his habit, acts, talk, etc and his personality actually bring him and other into danger position. Dr.Jekyll falls into stress and depression while the other (Mr.Utterson and Dr.Layon) are placed them into misunderstanding which build miscommunication because of low-level social communication from Dr.Jekyll to his friends. Keywords: individualism, independent, loner , uniqueness, bad impacts of being individualist. Abstrak Individualism telah menjadi trend dan telah diaplikasikan oleh penduduk di Negara-negara tertentu untuk menjadi kebiasaan dan kepribadian mereka. Individualisme berfokus pada konsep diri sendiri untur bertahan hidup. Skripsi ini bertujuan untuk merepresentasikan kepribadian individualistis dalam diri Dr.Jekyll dan pengaruh buruk terhadap dirinya dan orang lain karena kepribadian itu. Kajian ini menggunakan pendekatan individualisme dari Thomas Hobbes “Leviathan” dan John Stuart Mill “On Liberty” dan juga pemikiran-pemikiran lainuntuk mendukung kajian ini. Kajian ini akan menganalisis tentang bagaimana individualisme di represntakikan melalui Dr.Jekyll and bagaimana pengaruh buruknya terhadap dirinya dan orang lain. Penulis menggunakan tiga komponen untuk menunjukan individualisme, antara lain kemandirian, penyendiri, dan keunikan. Lalu untuk pengauh buruknya dibagi menjadi dua bagian ( diri sendiri dan orang lain) untuk menjelaskan bagaimana individualisme membawa situasi yang buruk untuk karakter. Hasilnya menunjukan bahwa Dr.Jekyll adalah seorang individualist sebenarnya yang terlihat dari kelakuan, aksi, perkatakaanya dan kepribadianya ini membawanya dan yang lain ke dalam posisi yang berbahaya. Dr.Jekyll jatuh dalam tekanan mental dan depresi sementara yang lain di letakanya dalam kesalahpahaman yang membentuk komunikasi yang berantakan karena keredahan level dari sebuah komunikasi kepada teman-temannya Kata Kunci: individualisme, kemandirian, penyendiri, keunikan, dampak buruk dari seorang individualist